A phase 1a, first-in-human, randomized study of a respiratory syncytial virus F protein vaccine with and without a toll-like receptor-4 agonist and stable emulsion adjuvant. Issue 25 (27th May 2016) - Falloon, Judith; Ji, Fei; Curtis, Craig; Bart, Stephan; Sheldon, Eric; Krieger, Diane; Dubovsky, Filip; Lambert, Stacie; Takas, Therese; Villafana, Tonya; Esser, Mark T.
Highlights: An RSV vaccine [F protein ± adjuvant] was assessed in subjects aged ≥60 years. Adjuvant contributed to local reactogenicity, but safety was acceptable. Adjuvant enhanced both humoral and cellular immune responses. A robust, antigen dose-dependent, F-specific IFN-γ T cell response was observed. Dose-dependent increases in humoral responses occurred. Abstract: Background: Respiratory syncytial virus (RSV) causes significant illness in older adults resulting in substantial health and economic impact. A successful vaccine would reduce morbidity in this growing segment of the population. Methods: In this double-blind phase 1 study, subjects 60 years of age and older were enrolled by cohort and randomized to receive vaccines containing escalating doses (20, 50, or 80 μg) of soluble RSV fusion protein (sF) alone or adjuvanted with 2.5 μg of glucopyranosyl lipid A, a toll-like receptor-4 agonist, in 2% stable emulsion (GLA-SE). Each cohort included 20 vaccine and 4 placebo recipients. Immune responses were evaluated using assays for RSV microneutralizing, anti-F IgG, and palivizumab competitive antibodies and for F-specific interferon (IFN)-γ enzyme-linked immunospot (ELISPOT) responses. Results: The inclusion of adjuvant increased local reactogenicity, with the majority of subjects who received sF and adjuvant reporting low-grade injection site pain or tenderness. At all doses, the safety profile was acceptable for further development. Immune responses were antigen dose-dependent, and the inclusion of adjuvant increased both humoral and cellular immune responses, with responses statistically higher than for placebo recipients in all 4 assays. At the highest dosage level with adjuvant, half of the subjects had a ≥3-fold rise from day 0 in RSV neutralizing antibody titers, and all had a ≥3-fold rise in antibody levels by anti-F IgG and palivizumab competitive antibody assays on day 29. For the day 8 IFNγ ELISPOT assay, 74% of subjects in the highest dosing cohort had a ≥3-fold rise from baseline. Conclusions: The safety and immunogenicity results from this study support inclusion of the GLA-SE adjuvant in this RSV vaccine for older adults and also support assessment of the efficacy of the vaccine in a larger clinical trial. Clinicaltrials.govNCT02115815 .